1989
DOI: 10.1177/030098588902600206
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Bovine Cutaneous Leukosis

Abstract: Biopsies of skin from a 2-year-old heifer with spontaneously regressing dermal leukosis were examined. The heifer was not infected with bovine leukemia virus and was negative for tumor-associated antigens of enzootic bovine lymphosarcoma. By hematological standards for bovine leukemia, the heifer was positive at about 60 days post-occurrence of the disease (POD). At 53 days POD, lymphoblastic neoplastic cells in the dermis reacted with anti-T lymphocyte monoclonal antibody by the avidin biotin peroxidase compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…The appearance of skin lesions in the present study was typical for bovine cutaneous lymphoma (Kadota et al 2001), but their distribution and rapid rate of growth were similar to those observed in only a few cases of T-cell lymphoma (Okada et al 1989;Peleteiro et al 2000;Klinkon and Cerne 2006) or dg T-cell lymphoma (Kadota et al 2001;Sato et al 2002). Rapid progression of the pathological process corresponded with a high proliferation activity of the lymphoma cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The appearance of skin lesions in the present study was typical for bovine cutaneous lymphoma (Kadota et al 2001), but their distribution and rapid rate of growth were similar to those observed in only a few cases of T-cell lymphoma (Okada et al 1989;Peleteiro et al 2000;Klinkon and Cerne 2006) or dg T-cell lymphoma (Kadota et al 2001;Sato et al 2002). Rapid progression of the pathological process corresponded with a high proliferation activity of the lymphoma cells.…”
Section: Discussionsupporting
confidence: 81%
“…Typically, the development of skin changes takes a few months (Stober 1981), but information about the case history is often scant (Schweizer et al 2003). The skin lesions started to appear three months after the first calving, as observed in a few other cases of T-cell cutaneous lymphomas in cattle (Okada et al 1989;Peleteiro et al 2000;Sato et al 2002). In two other described cases, the first tumours started to appear during pregnancy (Peleteiro et al 2000;Loh 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The observed changes in both plasma and urine are consistent with the changes seen in the classic clinical chemistry markers of nephrotoxicity. Cutaneous lymphosarcoma is a rare malignancy of horses and cattle (Janeski et al, 1996: Okada et al, 1989, with Bovine skin leukosis (Cutaneous lymphosarcoma) being one of the sporadic bovine leukoses which include calf, thymic and skin types. (Okada et al, 1989).…”
Section: P3 Fatty Acidmentioning
confidence: 99%
“…Cutaneous lymphosarcoma is a rare malignancy of horses and cattle (Janeski et al, 1996: Okada et al, 1989, with Bovine skin leukosis (Cutaneous lymphosarcoma) being one of the sporadic bovine leukoses which include calf, thymic and skin types. (Okada et al, 1989). Skin leukosis is usually seen in cattle 1 to 3 years old, with no sex or breed predilections and an extremely low incidence (one in three per million -Scott, 1988).…”
Section: P3 Fatty Acidmentioning
confidence: 99%
“…Erythrophagia by tumor cells was exceedingly rare. In the skin form of bovine lymphoma, the neoplastic cells characteristically involve the dermis with formation of Pautrier's microabscesses [7], but intraepidermal neoplastic cells were few in the tumor stage [11]. The thymic form is characterized by massive lymphoid infiltration of the thymus [20].…”
mentioning
confidence: 99%